МЕЖДОМЕТИЯ У МАРКО ЦЕПЕНКОВА - Nataliya V. Boronikova; Elena V. Verizhnikova (Philological Studies, 2019)
The paper on the material of the five-volume edition of the Macedonian tales collected by folklorist Marco Cepenkov, and his autobiography analyzed interjections typical of the Macedonian language late XIX – early XX centuries. The material presented in the creative heritage of M.Cepenkov, deserves a special lexicographic description, because it is not only rich and various, but captures the state of the Macedonian language well before the codification.